A novel conserved mutation in SGCE gene in 3 unrelated patients with classical phenotype myoclonus–dystonia syndrome. (July 2013) - Szubiga, Michał; Rudzińska, Monika; Bik-Multanowski, Mirosław; Pietrzyk, Jacek J; Szczudlik, Andrzej
Abstract : Objective and importance: Myoclonus–dystonia syndrome (MDS, DYT11) is an inherited disorder characterized by clinical and genetic heterogeneity. MDS is inherited in autosomal dominant pattern and caused by heterozygous mutations in the gene encoding epsilon-sarcoglycan (SGCE) on chromosome 7q21. SGCE gene mutations are present in about 30–50% patients classified as definite-MDS. Earlier onset of motor symptoms is indicated in MDS patients who are SGCE mutations carriers. We present clinical phenotype of three unrelated MDS patients bearing novel, not described yet, mutation in SGCE gene. Clinical presentation: Presence of a substantial mutation in exon 3, changing aspartic acid to asparagine in codon 96 (D96N) of SGCE protein has been revealed. Three unrelated individuals, bearing the same mutation have diversity of symptoms, with some common features. Age of onset of our patients differs: 2, 14 to 38 years of age. Intervention/technique: Detection of mutations in SGCE gene was performed via direct sequencing of SGCE gene. Conclusions: Our results confirm the role of the SGCE gene in the pathogenesis of MDS and call into question the impact of SGCE mutations on the age of onset. The existing list of known mutations and diversity of symptoms in patients bearing the same mutation indicates that there is a lack of genotype–phenotype correlation. Heterogeneity of disease indicates necessity for further research in order to find the molecular fingerprint which may be a landmark in diagnostic studies of MDS.